Accuracy of Intraocular Lens Power Calculation Using Anterior Chamber Depth from Two Devices with Barrett Universal II Formula. (23rd September 2019) - Muniz Castro, Hannah; Tai, Audrey X.; Sampson, Samuel J.; Wade, Matthew; Farid, Marjan; Garg, Sumit
Abstract : Purpose . To compare the preoperative measurements of the anterior chamber depth (ACD) by the IOLMaster and Catalys; additionally, to compare the accuracy of the IOL power calculated by the Barrett Universal II formula using the two different measurements. Setting . University of California, Irvine, Gavin Herbert Eye Institute in Irvine, California. Design . Retrospective comparative study. Methods . This study included 144 eyes of 90 patients with a mean age of 72.0 years (range 40.8 to 92.1 years) that underwent femtosecond laser-assisted cataract surgery using Catalys. Preoperative measurements of ACD were taken by the IOLMaster and Catalys. Manifest refraction and refractive spherical equivalent were measured 1 month postoperatively. Expected refractive results were compared with actual postoperative refractive results. Results . The correlation between the ACD values from the two devices was good ( r  = 0.80). The Catalys ACD measurements yielded a larger ACD compared to the IOLMaster, with a mean difference of 0.22 mm (P < 0.0001 ). The correlation between the postoperative and predicted RSE of the implanted IOL power was excellent ( r  = 0.96). There was no statistically significant difference between the mean absolute error derived from the IOLMaster, 0.37 diopter (D) ± 0.34 (SD), and the Catalys, 0.37 ± 0.35 D (P = 0.50 ). Conclusions . The Catalys biometry yielded a significantly larger ACD value than the IOLMaster. This difference in ACD value, however, did not reflect in a statistically significant difference in IOL power calculation and refractive prediction error using the Barrett Universal II Formula.